THE ROLE OF TEACHER AT SCHOOL TO IMPLEMENTING CLEAN AND HEALTHY LIFESTYLE BEHAVIOR IN STUDENTS OF SMK.N 1 PELEPAT - Ike Fitria Isnaini; Andicha Gustra Jeki; Dwiko Febrama Rizki; Puput Wahyu Hidayat (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The lack of implementation of Clean and Healthy Behavior (PHBS) is still a serious problem because it can cause transmission of various diseases. Basic Health research data (Ministry of Health) regarding PHBS of the population in general, Only 47% of Indonesia's population can properly wash their hands with soap. Teachers are professionals who can become facilitators, motivators, mentors, and models in changing the behavior of their students at school. By making it possible to reach teenagers through schools, the purpose of this research is to find out the relationship between the role of teachers in schools and the implementation of PHBS at SMK.N1 Pelepat in 2022. This quantitative research design is cross sectional. The sample in this student population is 45 people, which is determined randomly (simple random sampling). Data collection instrument using a questionnaire. The data obtained were analyzed by chi-square test, with a significance level of 95%. The results of this study indicate that there is a significant relationship between the role of teachers in schools and students' PHBS with a P-value of 0.047 (p≤0.05). For SMK.N 1 Pelepat this can be used as material for consideration in formulating policies related to the problem of implementing PHBS and providing information to students to always implement PHBS in schools